High valence metal doped single crystal lithium-rich manganese-based positive electrode material, preparation method thereof, positive electrode and battery
Patent Information
- Application Number
- CN202510932413.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-07
- Publication Date
- 2026-10-23
AI Technical Summary
[0005]本发明的目的是为了克服现有技术存在的能耗高、工艺复杂等问题,提供一种高价金属掺杂的单晶态富锂锰基正极材料及其制备方法、正极和电池
本发明提供了一种高价金属掺杂的单晶态富锂锰基正极材料,材料的表面包覆有包覆层,内部掺杂有高价金属元素。以高价金属取代部分Mn等金属阳离子,引入了一个更强的M-O键(M代表高价金属元素),有效改善了材料的结构稳定性。同时界面包覆层的引入改善了材料的界面副反应,减少了循环过程中电解液对体相的侵蚀。除此之外,添加的高价金属化合物在作为掺杂剂并构建包覆层的同时还起到了分散一次颗粒的作用,脉冲烧结后材料表现出明显的一次颗粒生长和分散性的增强。最终改性的富锂锰基正极材料展现出单晶态的形貌并表现出循环稳定性的提升和电压衰减的抑制。
Smart Images

Figure CN122968259A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of batteries, specifically to a high-valence metal-doped single-crystal lithium-rich manganese-based cathode material, its preparation method, cathode, and battery. Background Technology
[0002] With the continuous development of science and technology, portable mobile devices, electric vehicles, and other devices have entered our lives. Lithium-ion batteries, as a crucial component, have received widespread attention. Compared to traditional lead-acid and calomel batteries, lithium-ion batteries offer advantages such as high energy density, long lifespan, and lightweight design, meeting the needs of mobile devices and electric vehicles. They are particularly important in promoting the technological advancement and marketization of electric vehicles. As market demand continues to grow, the continuous development of lithium-ion batteries with higher energy density and longer cycle life has become crucial. Among these, the development of lithium-ion battery cathode materials is key to technological progress. Among various cathode materials, lithium-rich manganese-based cathode materials... Lithium-based materials (TM, including one or more of Ni, Co, and Mn, 0.5≤x<1.0, which can be abbreviated as LMR) have the characteristics of high operating potential and high specific capacity. In particular, cobalt-free lithium-rich manganese-based materials also take into account the characteristics of low cost and environmental friendliness, and therefore have attracted widespread attention.
[0003] The application of lithium-rich manganese-based materials currently faces several limitations. Firstly, the higher lithium content results in lower true and compaction densities compared to traditional cathode materials (such as lithium cobalt oxide and ternary systems), ultimately leading to reduced energy density. Secondly, the inherent kinetic properties of the material and poor structural stability after anion participation in redox reactions during charge and discharge cause voltage hysteresis, capacity degradation, and other issues. Recent research indicates that single-crystallization of lithium-rich materials can alleviate these problems to some extent. Single-crystallization can improve the mechanical strength of primary particles, enhance interfacial stability, and increase compaction density, leading to higher compaction densities and longer cycle lives, thus advancing the commercialization of lithium-rich manganese-based cathode materials.
[0004] Although lithium-rich manganese-based cathode materials have high discharge specific capacity during application, their actual energy density is low and their cycle performance is poor, often resulting in rapid capacity decay. However, single-crystal morphology design can effectively improve the mechanical stability of the material, reduce interfacial side reactions, thereby increasing energy density and improving cycle stability. Currently, there are three main approaches to completing single-crystal structure design. The first is sintering at higher temperatures. Due to the stronger bond energy of the Mn-O bond, this method often requires more energy than high-nickel single crystals. Furthermore, the volatilization of Li at high temperatures necessitates a larger Li source, making it difficult to implement industrially. The second approach is preparing small-particle-size single-crystal materials using sol-gel methods. Materials prepared using this method often exhibit better dispersibility and higher discharge specific capacity, but it is only suitable for small-scale laboratory preparations due to its complex and costly process. The third approach is the more common molten salt method. This method significantly lowers the preparation temperature due to the addition of molten salt, and the material also exhibits good dispersibility. However, molten salt often only provides a liquid environment, requiring water washing and subsequent tempering and sintering after preparation, increasing costs and potentially leading to reduced yield and increased process complexity. Summary of the Invention
[0005] The purpose of this invention is to overcome the problems of high energy consumption and complex processes in existing technologies, and to provide a single-crystal lithium-rich manganese-based cathode material doped with high-valence metals, its preparation method, cathode, and battery. The doping of this cathode material with high-valence metals results in larger primary particle sizes and reduced primary particle agglomeration, which is beneficial for improving the material's cycle stability and reducing voltage decay.
[0006] To achieve the above objectives, the first aspect of the present invention provides a single-crystal lithium-rich manganese-based cathode material doped with a high-valence metal, wherein the chemical formula of the cathode material is Li. a Ni b Mn 0.8-b-x M x O2, wherein M includes one or more metallic elements from Groups VB, VIB, IIIA, and VIA, with a valence not less than +3, 1.1 ≤ a ≤ 1.3, and 0.15 ≤ b ≤ 0.25. Based on the total molar amount of Ni and Mn in the cathode material, the value of x is chosen such that the amount of M is 0.5-2 mol%. The cathode material includes primary particles and secondary particles formed by the aggregation of primary particles. The average particle size of the primary particles is 0.2-3 μm, and the average particle size of the secondary particles is 1-6 μm.
[0007] The second aspect of the present invention provides a method for preparing a single-crystal lithium-rich manganese-based cathode material doped with a high-valence metal, wherein the preparation method includes: mixing a lithium-rich manganese-based precursor, a lithium source and a high-valence metal compound, and then performing a first sintering and a second sintering sequentially to obtain the cathode material; The temperature of the first sintering does not exceed 1000℃, the second sintering includes a third stage and a fourth stage, the temperature of the third stage is not lower than 1000℃, and the temperature of the fourth stage of the second sintering does not exceed 1000℃. The total amount of Ni and Mn in the lithium-rich manganese-based precursor and the molar ratio of lithium in the lithium source are 1:1-1.8, and the molar ratio of Ni and Mn in the lithium-rich manganese-based precursor is 1:2-5. The high-valence metal compound contains one or more metal elements from Group VB, Group VIB, Group IIIA, and Group VIA. The valence of the metal elements in the high-valence metal compound is not less than +3, preferably +5 and / or +6. Based on the total molar amount of Ni and Mn in the lithium-rich manganese-based precursor, the amount of metal elements in the high-valence metal compound is 0.5-2 mol.
[0008] A third aspect of the present invention provides a positive electrode, wherein the positive electrode comprises the positive electrode material described in the first aspect of the present invention or the positive electrode material prepared by the preparation method described in the second aspect of the present invention.
[0009] A fourth aspect of the present invention provides a lithium-ion battery, wherein the battery includes the positive electrode described in the third aspect of the present invention.
[0010] The cathode material prepared in this invention replaces some of the metal cations such as Mn with high-valence metal elements, thereby introducing stronger MO bonds and effectively improving the structural stability of the material. Simultaneously, the introduction of the interfacial coating layer improves interfacial side reactions and reduces electrolyte erosion of the bulk phase during cycling. Furthermore, the added high-valence metal compound acts as a dopant and constructs the coating layer while also dispersing primary particles. After pulse sintering, the material exhibits significant primary particle growth and enhanced dispersion. The resulting lithium-rich manganese-based cathode material displays a single-crystal morphology and demonstrates improved cycle stability and suppressed voltage decay. Attached Figure Description
[0011] Figure 1 The X-ray diffraction (XRD) patterns of the cathode materials prepared in Comparative Example 1 and Example 1 are shown. Figure 2 This is a scanning electron microscope (SEM) image of the cathode material prepared in Example 1; Figure 3 This is a transmission electron microscope (TEM) image of the cathode material prepared in Example 1; Figure 4 This is the Mo 3d pattern obtained by X-ray photoelectron spectroscopy (XPS) sputtering of the cathode material prepared in Example 1; Figure 5 This is a scanning electron microscope (SEM) image of the cathode material prepared in Example 2; Figure 6 This is a scanning electron microscope (SEM) image of the cathode material prepared in Example 3; Figure 7 This is a scanning electron microscope (SEM) image of the cathode material prepared in Example 4; Figure 8 This is a scanning electron microscope (SEM) image of the cathode material prepared in Example 5; Figure 9 This is a scanning electron microscope (SEM) image of the cathode material prepared in Comparative Example 1; Figure 10 This is a scanning electron microscope (SEM) image of the cathode material prepared in Comparative Example 2. Detailed Implementation
[0012] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0013] The terms “first”, “second”, etc. are used to distinguish similar objects, not to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate so that embodiments of this application can be implemented in orders other than those illustrated or described herein. The objects distinguished by “first”, “second”, etc. are usually of the same class and the number of objects is not limited. For example, the first object can be one or more.
[0014] Furthermore, the term "and / or" in the specification and claims is used to describe the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.
[0015] In the description of this application, unless otherwise stated, "a plurality of" means two or more.
[0016] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0017] In the field of battery materials, monocrystalline state refers to non-agglomerated monodisperse primary particles or primary particles with weak agglomeration (i.e., the secondary particles formed still maintain monocrystalline morphology), which is in stark contrast to the traditional polycrystalline morphology (which has spherical secondary particles composed of a large number of primary particles).
[0018] The first aspect of this invention provides a single-crystal lithium-rich manganese-based cathode material doped with a high-valence metal, wherein the chemical formula of the cathode material is Li. a Ni b Mn 0.8-b-x M x O2, wherein M includes one or more metallic elements from Groups VB, VIB, IIIA, and VIA, with a valence not less than +3, 1.1 ≤ a ≤ 1.3, and 0.15 ≤ b ≤ 0.25. Based on the total molar amount of Ni and Mn in the cathode material, the value of x is chosen such that the amount of M is 0.5-2 mol%. The cathode material includes primary particles and secondary particles formed by the aggregation of primary particles. The average particle size of the primary particles is 0.2-3 μm, and the average particle size of the secondary particles is 1-6 μm.
[0019] The cathode material prepared by this invention includes primary particles and secondary particles formed by the agglomeration of primary particles. By combining the size of the secondary particles with the size of the primary particles, it can be seen that the primary particles of the cathode material prepared by this invention have good dispersibility and low agglomeration. The average particle size of the primary particles in this invention can be 0.2μm, 0.3μm, 0.4μm, 0.6μm, 0.8μm, 1μm, 1.2μm, 1.4μm, 1.5μm, 2μm, 2.5μm, 3μm, or any value between any two of these values. The average particle size of the secondary particles can be 1μm, 1.5μm, 1.8μm, 2μm, 2.3μm, 2.5μm, 3μm, 4μm, 5μm, 6μm, or any value between any two of these values.
[0020] The values of a and b can be chosen to conform to the requirements of lithium-rich manganese-based materials. The value of a can be 1.1, 1.15, 1.2, 1.25, 1.3, or any value between any two of them. The value of b can be 0.15, 0.17, 0.19, 0.2, 0.22, 0.25, or any value between any two of them. The value of x can be chosen to make the amount of M 0.5 mol%, 0.7 mol%, 0.9 mol%, 1 mol%, 1.2 mol%, 1.5 mol%, 1.7 mol%, 2 mol%, or any value between any two of them.
[0021] Preferably, the average particle size of the primary particles is 1-1.5 μm, and the average particle size of the secondary particles is 1.5-2.5 μm.
[0022] Preferably, the compacted density of the material is 2-3.5 g / cm³. 3 For example, it could be 2g / cm 3 2.3g / cm 3 2.5g / cm 3 2.8g / cm 3 3g / cm 3 3.3g / cm 3 3.5g / cm 3 and any value between any two of them.
[0023] Preferably, the compaction density of the positive electrode material is 3-3.5 g / cm³. 3 .
[0024] Preferably, the oxidation state of M is +5 and / or +6.
[0025] Preferably, the value of x is such that the amount of M is 0.8-1.3 mol.
[0026] The method for testing the compaction density of the present invention is as follows: The positive electrode material, Super P, and PVDF (polyvinylidene fluoride) were dispersed in NMP (N-methyl-2-pyrrolidone) at a ratio of 8:1:1. The mixture was then thoroughly mixed in a mortar and uniformly coated onto aluminum foil (current collector), and dried in a vacuum oven at 60°C for 12 hours. The resulting material was then cut into 11 mm diameter discs. 80% of the difference between the mass of the prepared electrode disc (disc) and the mass of the blank aluminum foil was taken as the mass of the active material. The mass of the active material divided by the electrode disc area was taken as the areal density of the prepared electrode disc. The disc was then compacted using a roller press at 20 MPa (generally repeated 3 times). The thickness of the compacted electrode disc was measured, and the compacted density was calculated as: areal density / (thickness of the compacted electrode disc - thickness of the current collector).
[0027] The second aspect of the present invention provides a method for preparing a single-crystal lithium-rich manganese-based cathode material doped with a high-valence metal, wherein the preparation method includes: mixing a lithium-rich manganese-based precursor, a lithium source and a high-valence metal compound, and then performing a first sintering and a second sintering sequentially to obtain the cathode material; The temperature of the first sintering does not exceed 1000℃, the second sintering includes a third stage and a fourth stage, the temperature of the third stage is not lower than 1000℃, and the temperature of the fourth stage of the second sintering does not exceed 1000℃. The total amount of Ni and Mn in the lithium-rich manganese-based precursor and the molar ratio of lithium in the lithium source are 1:1-1.8, and the molar ratio of Ni and Mn in the lithium-rich manganese-based precursor is 1:2-5. The high-valence metal compound contains one or more metal elements from Group VB, Group VIB, Group IIIA, and Group VIA. The valence of the metal elements in the high-valence metal compound is not less than +3, preferably +5 and / or +6. Based on the total molar amount of Ni and Mn in the lithium-rich manganese-based precursor, the amount of metal elements in the high-valence metal compound is 0.5-2 mol.
[0028] The cathode material prepared by this invention comprises a core and a coating layer. The coating layer is a high-valence lithium salt, Li₂MO₄. The presence of the coating can reduce the erosion of POF₃ and HF generated by the reaction of LiPF₆ and trace water in the electrolyte, thereby improving interfacial stability. Furthermore, it benefits from the stronger bond strength of the high-valence metal, such as (Mo-O: ≈607.1 KJ mol⁻¹). -1 Cr-O: ≈590 kJ mol -1 VO: ≈543 kJ mol -1 WO: ≈598-632 kJ·mol −1 The bond energy of the Ni / Mn-O bond (Mn-O: ≈402 kJ·mol) −1 Ni-O: ≈391.6 kJ·mol −1 This process enables a tighter bond between the Ni / Mn-O layers, preventing Ni / Mn ions from migrating into the Li layer. The resulting single-crystal lithium-rich manganese-based cathode material exhibits good dispersibility, better mechanical strength, and stronger structural stability. Consequently, the cycling stability of the material is significantly improved; after 100 cycles at 1C, it retains nearly 100% capacity retention, while voltage decay is effectively suppressed.
[0029] The amount of high-valence metal compound incorporated affects the morphology and electrochemical performance of the cathode material. When the doping amount is too low, the primary particle size of the material is small, and the improvement in electrochemical performance is not significant. When the doping amount is too high, although the primary particle size of the material increases, the electrochemical performance decreases. Based on the total molar amount of Ni and Mn in the lithium-rich manganese-based precursor, the doping amount of high-valence metal compound can be 0.5 mol%, 0.8 mol%, 1.0 mol%, 1.2 mol%, 1.3 mol%, 1.5 mol%, 1.8 mol%, 2 mol%, and any value between any two of them.
[0030] Preferably, the high-valence metal compound includes oxides of high-valence metals and / or salts of high-valence metals.
[0031] Preferably, the high-valence metal compound includes MoO3, TeO2 (NH4)6W7O 24 One or more of 6H2O, Tl2O3, and SeO2.
[0032] Preferably, the high-valence metal compound is MoO3.
[0033] Since some lithium will volatilize during sintering, an excess of lithium source needs to be added when mixing lithium. The molar ratio of the total amount of Ni and Mn in the lithium-rich manganese-based precursor to the molar amount of lithium in the lithium source can be 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, or any value between any two of these.
[0034] Preferably, the molar ratio of Ni and Mn elements in the lithium-rich manganese-based precursor to that of lithium element in the lithium source is 1:1.5-1.7.
[0035] Preferably, based on the total amount of Ni and Mn elements in the lithium-rich manganese-based precursor, the amount of metal elements in the high-valence metal compound is 0.8-1.3 mol.
[0036] The molar ratio of Ni to Mn in the lithium-rich manganese-based precursor selected in this invention can be 1:2, 1:3, 1:4, 1:5, or any value between any two of these numbers.
[0037] Preferably, the molar ratio of Ni to Mn in the lithium-rich manganese-based precursor is 1:2-4.
[0038] Both the first and second sintering were carried out in an air atmosphere.
[0039] Preferably, the first sintering includes a first stage and a second stage. The temperature of the first stage is 400-600℃, such as 400℃, 450℃, 500℃, 550℃, 600℃ and any value between any two of them, and the holding time is 3-5h, such as 3h, 3.5h, 4h, 4.5h, 5h and any value between any two of them. The temperature of the second stage is 700-900℃, such as 700℃, 750℃, 800℃, 850℃, 900℃ and any value between any two of them, and the holding time is 3-5h, such as 3h, 3.5h, 4h, 4.5h, 5h and any value between any two of them.
[0040] Preferably, the temperature of the third stage is 1000-1100℃, such as 1000℃, 1020℃, 1040℃, 1060℃, 1080℃, 1100℃ and any value between any two of them, and the heat preservation time is 3-10min, such as 3min, 5min, 7min, 9min, 10min and any value between any two of them.
[0041] Preferably, the heating rate in the third stage is 5-300℃ / min, such as 5℃ / min, 10℃ / min, 15℃ / min, 30℃ / min, 50℃ / min, 100℃ / min, 150℃ / min, 200℃ / min, 250℃ / min, 300℃ / min, and any value between any two of these numbers.
[0042] Preferably, the heating rate in the third stage is 5-15℃ / min.
[0043] Preferably, the temperature of the fourth stage is 700-900℃, such as 700℃, 720℃, 750℃, 800℃, 850℃, 880℃, 900℃ and any value between any two of them, and the time is 3-5h, such as 3h, 3.5h, 4h, 4.5h, 5h and any value between any two of them.
[0044] Preferably, the cooling rate of the fourth stage is 5-300℃ / min, such as 5℃ / min, 10℃ / min, 15℃ / min, 30℃ / min, 50℃ / min, 100℃ / min, 150℃ / min, 200℃ / min, 250℃ / min, 300℃ / min, and any value between any two of them.
[0045] Preferably, the cooling rate in the fourth stage is 5-15℃ / min.
[0046] Preferably, the average particle size of the lithium-rich manganese-based precursor is 4-5 μm. Unlike traditional preparation methods, the lithium-rich manganese-based precursor of the present invention has a smaller average particle size. The smaller precursor has a larger specific surface area and higher activity, which is beneficial for further promoting the formation of primary particles.
[0047] Preferably, the lithium source includes lithium carbonate and / or lithium hydroxide. This invention does not have special requirements for the lithium source; any commonly used lithium source in the art, such as lithium carbonate or lithium hydroxide, is acceptable and can be obtained commercially.
[0048] The method further includes: the mixing is carried out in the presence of a solvent. There are no particular requirements for the type of solvent; any commonly used solvents in the art are acceptable, such as anhydrous ethanol. The role of the solvent is to provide a liquid environment, which is beneficial for further promoting particle dispersion.
[0049] The method for preparing the lithium-rich manganese-based precursor includes: in the presence of nitrogen, using ammonia water as the base liquid, adding a salt solution containing transition metal elements, a precipitant, and a chelating agent, and carrying out a co-precipitation reaction to obtain the lithium-rich manganese-based precursor, wherein the molar ratio of Ni to Mn in the salt solution containing transition metal elements is 1:2-5.
[0050] There are no particular requirements for the specific types of Ni and Mn salts in the salt solution containing transition metal elements; any commonly used salts in the field are acceptable, such as NiSO4·6H2O and MnSO4·H2O. The concentration of the salt solution containing transition metal elements can be 1-5M, such as 1M, 2M, 3M, 4M, 5M, or any two of these values, preferably 2-4M. The molar ratio of Ni to Mn in the salt solution containing transition metal elements is 1:2-4.
[0051] Preferably, the temperature of the coprecipitation reaction is 40℃-70℃, such as 40℃, 50℃, 60℃, 70℃ and any two of these values; the time is 10-20h, such as 10h, 12h, 14h, 16h, 18h, 20h and any two of these values; and the pH is 10.5-11.5, such as 10.5, 10.8, 11.0, 11.2, 11.5 and any two of these values.
[0052] Preferably, the concentration of the ammonia water used as the base liquid is 0.3-0.4M, such as 0.3M, 0.35M, 0.36M, 0.4M, and any two of these values.
[0053] Preferably, the chelating agent is ammonia water, and the concentration of the chelating agent is controlled to be 5-8M based on the total amount of the chelating agent, such as 5M, 6M, 7M, 8M and any two of these values.
[0054] Preferably, the precipitant comprises a sodium hydroxide solution, and its concentration is 5-10M based on the total amount of the sodium hydroxide solution, such as 5M, 6M, 7M, 8M, 9M, 10M and any two of these numbers, preferably 5-8M.
[0055] Preferably, the coprecipitation reaction is carried out under stirring at a speed of 800-1000 rpm, such as 800 rpm, 900 rpm, 1000 rpm, or any two of these values.
[0056] Preferably, the preparation method of the lithium-rich manganese-based precursor further includes: after the co-precipitation reaction is completed, the product is washed with deionized water and dried at 80-100℃ for 10-15h to obtain the lithium-rich manganese-based precursor.
[0057] A third aspect of the present invention provides a positive electrode, wherein the positive electrode comprises the positive electrode material described in the first aspect of the present invention or the positive electrode material prepared by the preparation method described in the second aspect of the present invention.
[0058] A fourth aspect of the present invention provides a lithium-ion battery, wherein the battery includes the positive electrode described in the third aspect of the present invention.
[0059] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a single-crystal lithium-rich manganese-based cathode material doped with a high-valence metal. The material has a coating layer on its surface and is doped with a high-valence metal element internally. Replacing some Mn and other metal cations with a high-valence metal introduces a stronger MO bond (M represents a high-valence metal element), effectively improving the material's structural stability. Simultaneously, the introduction of the interfacial coating layer improves interfacial side reactions and reduces electrolyte erosion of the bulk phase during cycling. Furthermore, the added high-valence metal compound acts as a dopant and contributes to the coating layer while also dispersing primary particles. After pulse sintering, the material exhibits significant primary particle growth and enhanced dispersion. The final modified lithium-rich manganese-based cathode material exhibits a single-crystal morphology and demonstrates improved cycle stability and suppressed voltage decay.
[0060] This invention also provides a method for preparing a single-crystal lithium-rich manganese-based substrate material induced by high-valence metal compounds and pulse sintering, and simultaneously achieves the doping and surface coating of high-valence metals. This method ensures that the resulting material forms a lithium salt coating layer containing high-valence metal elements and a single-crystal morphology by mixing a hydroxide precursor, a high-valence metal compound (such as MoO3), and a lithium source, and then performing staged pulse sintering.
[0061] The present invention will be described in detail below through examples. Unless otherwise specified, all reagents or instruments used in the following examples are commercially available conventional products. Where specific conditions are not specified in the examples, conventional conditions or conditions recommended by the manufacturer shall apply.
[0062] In the following examples and comparative examples, the test methods are as follows: (1) Compacted density test method: The positive electrode material, Super P, and PVDF (polyvinylidene fluoride) were dispersed in NMP (N-methyl-2-pyrrolidone) at a ratio of 8:1:1. The mixture was then thoroughly mixed in a mortar and uniformly coated onto aluminum foil (current collector), and dried in a vacuum oven at 60°C for 12 hours. The resulting material was then cut into 11 mm diameter discs. 80% of the difference between the mass of the prepared electrode disc (disc) and the mass of the blank aluminum foil was taken as the mass of the active material. The areal density of the prepared electrode disc was calculated as the active material mass divided by the electrode disc area. The disc was then compacted using a roller press at 20 MPa (approximately repeated 3 times). The thickness of the compacted electrode disc was measured, and the compacted density was calculated as: areal density / (thickness of the compacted electrode disc - thickness of the current collector).
[0063] (2) XRD test: The instrument used was Rigaku Dmax-2400, Japan.
[0064] (3) SEM test: The instrument used was S-4800, Japan.
[0065] (4) XPS test: The instrument used was AXIS SUPRA+, Japan.
[0066] (5) TEM test: The instrument used was JEM-2100, Japan.
[0067] (6) Raman test: The instrument used was Renishaw inVia, UK.
[0068] (7) Battery assembly: Using the materials prepared in the examples or comparative examples as active materials, the active materials are mixed with Super P and PVDF (polyvinylidene fluoride) at a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) is added and ground into a slurry. The slurry is then coated onto aluminum foil using a 125-micron scraper, dried, and cut into positive electrode sheets; then, in an argon glove box (water < 0.01... Oxygen < 0.01 The CR2032 coin cell is assembled in the above-mentioned positive electrode, the counter electrode is a lithium sheet, the separator is Celgard 2500, and the electrolyte is a solution prepared with EC (ethylene carbonate) and DMC (dimethyl carbonate) in a volume ratio of 1:1 as solvents and 1 mol / L LiPF6 as solute.
[0069] (7) Battery performance test: A LAND CT 2001A tester was used, which was purchased from Wuhan Landian Electronics Co., Ltd. At 30℃, the battery was charged and discharged at 0.1 C (1 C = 200 mA / g) in the voltage range of 2.0 V to 4.8 V for 2 weeks, and then charged and discharged at 1 C in the voltage range of 2.0 V to 4.8 V for 100 cycles.
[0070] Preparation Example 1 Nitrogen gas was introduced into the reactor. A 0.36 M dilute ammonia solution was pumped into the reactor as a base solution using a peristaltic pump. A 3 M salt solution containing transition metal elements was added to the reactor. The nickel salt used in the salt solution containing transition metal elements was NiSO4·6H2O, and the manganese salt was MnSO4·H2O. The molar ratio of Ni to Mn in the salt solution containing transition metal elements was 1:3. Simultaneously, a 6 M chelating agent (ammonia) and a 6 M precipitant (sodium hydroxide) solution were pumped in. The mixture was stirred at 55°C for 15 hours, and the pH of the reactor was controlled at approximately 11.2. The stirring speed was 1000 rpm.
[0071] After the reaction was completed, the mixture was aged for 12 h. The precipitate was then washed with deionized water, filtered, and dried (90℃, 13 h) to obtain a lithium-rich manganese-based precursor with an average particle size of 4.17 μm. The chemical formula of the lithium-rich manganese-based precursor is Ni. 0.25 Mn 0.75 (OH)2.
[0072] The use of higher transition metal salt solution concentration, ammonia concentration, and stirring temperature in this preparation example is beneficial for generating lithium-rich manganese-based precursors with smaller particle size.
[0073] Preparation Example 2 The preparation was carried out in the same manner as in Example 1, except that the concentration of the salt solution containing the transition metal element was 1M, the concentration of the chelating agent ammonia was 4M, and the coprecipitation temperature was 30°C. The average particle size of the obtained lithium-rich manganese-based precursor was 5.6 μm.
[0074] Example 1 Preparation and analysis of lithium-rich manganese-based cathode materials Accurately weigh 0.054 mol LiOH·H2O, 0.0003 mol MoO3 and 0.033 mol of the lithium-rich manganese-based precursor from Preparation Example 1, wherein the molar ratio of the total amount of Ni and Mn elements in the lithium-rich manganese-based precursor to the molar ratio of Li element in LiOH is 1:1.65, and the Mo element in MoO3 accounts for 1 mol of the total amount of Ni and Mn elements in the lithium-rich manganese-based precursor.
[0075] A lithium-rich manganese-based precursor, LiOH·H2O, and MoO3 were mixed evenly in a mortar, and approximately 20 mL of anhydrous ethanol was added. The mixture was then ground for about 20 minutes until the anhydrous ethanol was completely evaporated. The mixture was spread evenly in a porcelain boat and placed in a muffle furnace. Under air atmosphere, the temperature was increased to 500 °C at 2 °C / min and sintered for 3 hours. Then, the temperature was increased to 900 °C at 2 °C / min and sintered for 3 hours. Subsequently, the temperature was increased to 1100 °C at 10 °C / min and sintered for 10 minutes. Finally, the temperature was decreased to 900 °C at 10 °C / min and sintered for 3 hours to obtain a 1 mol% Mo-doped lithium-rich manganese-based cathode material. The chemical formula of this material is Li. 1.2 Ni 0.2 Mn 0.592 Mo 0.008 O2.
[0076] The XRD test results of the prepared lithium-rich manganese-based cathode material are as follows: Figure 1 As shown, the cathode material exhibits distinct peak splitting at the (006) / (102) peak near 38°(2θ) and the (108) / (110) peak near 65°(2θ), indicating a well-formed layered structure without obvious impurity peaks, which is beneficial for Li + The insertion and extraction of [the material] are observed. The superlattice peak near 22° (2θ) is a characteristic peak of the Li2MnO3 phase in the cathode material, reflecting the unique honeycomb superstructure unit. The structure is consistent with that of the material prepared in Comparative Example 1, indicating that doping did not significantly alter the crystal structure of the material.
[0077] SEM images of the cathode material are shown below. Figure 2 As shown, compared with Comparative Example 1, the material exhibits significant particle size dispersion and primary particle growth after pulse sintering and the incorporation of MoO3, with the primary particle size reaching 1 μm.
[0078] TEM image test results of the cathode material are as follows Figure 3 As shown, Figure 3 The first small image I in the first horizontal row of the right-hand image, and the first small image I in the second horizontal row. Figure II And the first small one in the third row Figure III The images on the left correspond to magnified views of regions I, II, and III, respectively. The smaller images in the second and third columns of the right image correspond to the Fourier transform and inverse Fourier transform of the smaller image in the first column, respectively. Regions I, II, and III correspond to the material surface and bulk phase, respectively. The images show that the lattice spacing in region I is 2.27 Å, corresponding to the (241) crystal plane of Li₂MoO₄ (PDF#12-0763), indicating that Li₂MoO₄ is coated on the material surface. Region II shows a small amount of spinel phase (dot-like inclusions between horizontal stripes), which may be related to Mo… 6+ The introduction of [something] is related to the fact that region III is the bulk phase diagram of the material, and its surface bulk phase has a layered structure.
[0079] XPS test results of cathode materials are as follows Figure 4 As shown in the figure, and considering the peak on the right, it can be seen that after the material is doped with MoO3 and undergoes pulse sintering, MoO3 is formed in the material. 6+ The doping of Mo, after sputtering, extends from the surface to the bulk phase (0nm-40nm). 6+ The content of [Mo] decreased slightly. XPS test results indicate that Mo was introduced into the material. 6+ .
[0080] Example 2 The process was carried out in accordance with Example 1, with the only difference being that: MoO3 was 0.00017 mol, and in the lithium-rich manganese-based cathode material, the amount of Mo was 0.5 mol based on the total amount of Ni and Mn elements.
[0081] The SEM test results of the material prepared in this embodiment are as follows: Figure 5 As shown, compared with Comparative Example 1 Figure 9 In comparison, the primary particles in the material have a significantly increased particle size, better dispersibility, and lower agglomeration.
[0082] Example 3 The procedure was carried out in accordance with Example 1, except that MoO3 was replaced with an equimolar amount of V2O5.
[0083] The SEM test results of the material prepared in this embodiment are as follows: Figure 6 As shown, compared with Comparative Example 1 Figure 9 In comparison, the particle size of the primary particles in the material has increased significantly, the dispersibility is better, and the particle size of the primary particles has changed from plate-like to cubic.
[0084] Example 4 The process was carried out in accordance with Example 1, except that sintering at 1100°C for 10 minutes was replaced with sintering at 1000°C for 10 minutes.
[0085] The SEM test results of the material prepared in this embodiment are as follows: Figure 7 As shown, the particle size of the primary particles in the material has increased significantly and the dispersion is good. However, compared with Example 1, the particle production is not sufficient and there are more small particles that have not grown.
[0086] Example 5 The procedure was carried out in accordance with Example 1, except that MoO3 was replaced with an equimolar amount of (NH4)6H2W. 12 O 40 ·6H2O.
[0087] The SEM test results of the material prepared in this embodiment are as follows: Figure 8 As shown, after the material is sintered with the introduction of ammonium metatungstate, the particle size of the primary particles increases to a certain extent, but the surface of the material shows a certain degree of corrosion.
[0088] Example 6 The process was carried out in accordance with Example 1, except that the amount of MoO3 was 0.05 mol, and the amount of Mo doping in the resulting material was 1.5 mol based on the total amount of Ni and Mn.
[0089] Example 7 The procedure was carried out in accordance with Example 1, except that the sintering time at 1100°C was 5 minutes.
[0090] Example 8 The procedure was carried out in accordance with Example 1, except that the temperature was increased to 1100°C at a rate of 30°C / min and sintered for 10 min.
[0091] Example 9 The procedure was carried out in accordance with Example 1, except that the lithium-rich manganese-based precursor was derived from Preparation Example 2.
[0092] Example 10 The procedure was carried out in accordance with Example 1, except that MoO3 was replaced with an equimolar amount of MoO2.
[0093] Comparative Example 1 The only difference from Example 1 is that MoO3 is not added to the raw materials, and the preparation method is as follows: A lithium-rich manganese-based precursor and LiOH·H2O were mixed evenly in a mortar, and anhydrous ethanol was added. Grinding continued for about 20 minutes until the ethanol was completely evaporated. The mixture was then spread evenly in a porcelain boat and placed in a muffle furnace. Sintering was carried out in air at a rate of 5℃ / min to 500℃ for 3 hours, followed by a further increase in temperature to 2℃ / min to 900℃ for 12 hours. The resulting lithium-rich manganese-based cathode material had no coating layer on its surface. Its chemical formula is: Li 1.2 Mn 0.6 Ni 0.2 O2.
[0094] The XRD test results of the material prepared in this embodiment are as follows: Figure 1 As shown, the material exhibits distinct peak divisions at the (006) / (102) peak near 38°(2θ) and the (108) / (110) peak near 65°(2θ), indicating the formation of a well-defined layered structure.
[0095] The SEM test results of the material prepared in this embodiment are as follows: Figure 9As shown, the primary particle size of the material is mainly between 200-400 nm, and it exhibits a very obvious agglomeration phenomenon. Compared with the precursor diagram, the particle size of the prepared material is smaller. This is mainly due to the lack of doping with high-valence metal elements and the absence of pulse sintering. During the sintering process, the particle size of the precursor is insufficient after dispersion. It can be seen that compared with the pulse sintering of the present invention, the traditional sintering method, due to the lack of short-time sintering at high temperature, cannot improve the performance of the material even with extended sintering time (900℃, 12h).
[0096] Comparative Example 2 The procedure was carried out in accordance with Example 1, except that MoO3 was not added.
[0097] The SEM test results of the material prepared in this embodiment are as follows: Figure 10 As shown in the figure, compared with Comparative Example 1, although the particle size of the primary particles in the material prepared in this example has increased, the dispersion of the primary particles is insufficient, and the agglomeration phenomenon is very obvious. The material was assembled into a battery, and its electrochemical performance was tested. The test results are shown in Table 1.
[0098] The particle size and compaction density of the materials prepared in Examples 1-10 and Comparative Examples 1-2 were tested, and the results are shown in Table 1.
[0099] Table 1
[0100] The materials prepared in Examples 1-10 and Comparative Examples 1-2 were assembled into batteries, and their electrochemical performance was tested. The results are shown in Table 2.
[0101] Table 2
[0102] As can be seen from Tables 1 and 2, the primary particles of the lithium-rich manganese-based cathode material prepared by this invention show significant growth and improved dispersion, while the cycle stability and voltage decay are effectively mitigated.
[0103] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A single-crystal lithium-rich manganese-based cathode material doped with a high-valence metal, characterized in that, The chemical formula of the positive electrode material is Li a Ni b Mn 0.8-b-x M x O2, wherein M includes one or more metallic elements from Groups VB, VIB, IIIA, and VIA, with a valence not less than +3, 1.1 ≤ a ≤ 1.3, and 0.15 ≤ b ≤ 0.
25. Based on the total molar amount of Ni and Mn in the cathode material, the value of x is chosen such that the amount of M is 0.5-2 mol%. The cathode material includes primary particles and secondary particles formed by the aggregation of primary particles. The average particle size of the primary particles is 0.2-3 μm, and the average particle size of the secondary particles is 1-6 μm.
2. The cathode material according to claim 1, wherein, The average particle size of the primary particles is 1-1.5 μm, and the average particle size of the secondary particles is 1.5-2.5 μm; Preferably, the compaction density of the positive electrode material is 2-3.5 g / cm³. 3 Preferably 3-3.5 g / cm³ 3 ; Preferably, the oxidation state of M is +5 and / or +6; Preferably, the value of x is such that the amount of M is 0.8-1.3 mol.
3. A method for preparing a high-valence metal-doped single-crystal lithium-manganese-based cathode material, characterized in that, The preparation method includes: mixing a lithium-rich manganese-based precursor, a lithium source, and a high-valence metal compound, and then sequentially performing a first sintering and a second sintering to obtain the cathode material; The temperature of the first sintering does not exceed 1000℃, the second sintering includes a third stage and a fourth stage, the temperature of the third stage is not lower than 1000℃, and the temperature of the fourth stage of the second sintering does not exceed 1000℃. The total amount of Ni and Mn in the lithium-rich manganese-based precursor and the molar ratio of lithium in the lithium source are 1:1-1.8, and the molar ratio of Ni and Mn in the lithium-rich manganese-based precursor is 1:2-5. The high-valence metal compound contains one or more metal elements from Group VB, Group VIB, Group IIIA, and Group VIA. The valence of the metal elements in the high-valence metal compound is not less than +3, preferably +5 and / or +6. Based on the total molar amount of Ni and Mn in the lithium-rich manganese-based precursor, the amount of metal elements in the high-valence metal compound is 0.5-2 mol.
4. The preparation method according to claim 3, wherein, The high-valence metal compounds include oxides of high-valence metals and / or salts of high-valence metals; Preferably, the high-valence metal compound includes MoO3, TeO2 (NH4)6W7O 24 One or more of ·6H2O, Tl2O3, and SeO2, preferably MoO3.
5. The preparation method according to claim 3 or 4, wherein, The molar ratio of the total amount of Ni and Mn in the lithium-rich manganese-based precursor to the molar amount of lithium in the lithium source is 1:1.5-1.
7. And / or, based on the total amount of Ni and Mn elements in the lithium-rich manganese-based precursor, the amount of metal elements in the high-valence metal compound is 0.8-1.3 mol%; And / or, the molar ratio of Ni to Mn in the lithium-rich manganese-based precursor is 1:2-4.
6. The preparation method according to any one of claims 3-5, wherein, The temperature of the third stage is 1000-1100℃, and the holding time is 3-10 minutes; Preferably, the heating rate in the third stage is 5-300℃ / min, more preferably 5-15℃ / min; And / or, The fourth stage is characterized by a temperature of 700-900℃ and a duration of 3-5 hours. Preferably, the cooling rate in the fourth stage is 5-300℃ / min, and more preferably 5-15℃ / min.
7. The preparation method according to any one of claims 3-6, wherein, The average particle size of the lithium-rich manganese-based precursor is 4-5 μm; And / or, the lithium source includes lithium carbonate and / or lithium hydroxide.
8. The preparation method according to any one of claims 3-7, wherein, The first sintering includes a first stage and a second stage. The temperature of the first stage is 400-600℃ and the holding time is 3-5h. The temperature of the second stage is 700-900℃ and the holding time is 3-5h.
9. A positive electrode, characterized in that, The positive electrode includes the positive electrode material according to claim 1 or 2, or the positive electrode material prepared by the preparation method according to any one of claims 3-8.
10. A lithium-ion battery, characterized in that, The battery includes the positive electrode as described in claim 9.